Neo-luddism in the shadow of luddism - ÖCAL, ASLAN TOLGA (My University, 2023)
echnology is adopted regardless of its results; however, technology does not always result in absolute progress. The Luddites, the first movement to resist the effects of technology, made a series of uprisings in the nineteenth century, and even today they represent anxiety against technology. Neo-Luddism, as the successor of Luddism, peacefully opposes technology’s adverse effects with a distinct identity. This study evaluates the role Neo-Luddites can play in countering technology’s consequences. The study examines the Neo-Luddite perspective on technology, which seeks to find its own identity between the optimism of scientism in the technographic world and the pessimism of Luddism, considering the consequences of technology on employment and work. Neo-Luddites should emphasize technology’s political side, establish an identity, and determine their methods. Through these efforts, Neo-Luddites can raise awareness of technology’s adverse effects, build pressure on social policies and legal regulations, and shape society’s perspective of technology.